Graphene aerogel inorganic-organic solid electrolyte composite separator and preparation method thereof
Patent Information
- Application Number
- CN202311484762.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-08
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-08
AI Technical Summary
传统锂离子电池中聚合物隔膜机械强度较低,容易被负极析出的锂枝晶刺穿,造成电池短路放热,导致电解液燃烧爆炸,存在较大安全隐患
[0014]本发明提供了一种石墨烯气凝胶无机有机固态电解质复合隔膜的制备方法,本方法利用氧化石墨烯,制备具有三维骨架结构的石墨烯气凝胶,增加了隔膜的机械强度;通过使得无机固态电解质附着在三维骨架上形成三维网络结构,增加了锂离子的传导效率;加入有机固态电解质,增加了隔膜的柔韧性,同时进一步增加了隔膜的机械强度。本方法制备得到的GA有机无机固态电解质复合隔膜,可以应用在锂离子电池中,不但提高了锂离子的传导效率,还提升了锂离子的安全性。
Smart Images

Figure CN117335002B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery separator technology, and more particularly to graphene aerogel inorganic-organic solid electrolyte composite separator and its preparation method. Background Technology
[0002] With the development and popularization of new energy electric vehicles, the market is placing increasingly higher demands on the energy density and safety of power batteries. Traditional lithium-ion batteries suffer from polymer separators with low mechanical strength, making them susceptible to puncture by lithium dendrites deposited at the negative electrode. This can cause short circuits, heat release, and even electrolyte combustion and explosion, posing significant safety hazards. Organic-inorganic composite solid-state electrolytes, possessing both good lithium-ion conductivity and excellent mechanical strength, hold great promise for overcoming the two major problems faced by traditional lithium-ion batteries: low energy density and poor safety, thus greatly improving the safety of lithium-ion batteries. Summary of the Invention
[0003] The purpose of this invention is to provide a graphene aerogel inorganic-organic solid electrolyte composite membrane and its preparation method. This method utilizes graphene oxide to prepare graphene aerogel with a three-dimensional framework structure, which increases the mechanical strength of the membrane. By attaching the inorganic solid electrolyte to the three-dimensional framework to form a three-dimensional network structure, the lithium-ion conduction efficiency is increased. The addition of organic solid electrolyte increases the flexibility of the membrane and further increases its mechanical strength.
[0004] Therefore, in a first aspect, embodiments of the present invention provide a method for preparing a graphene aerogel inorganic-organic solid electrolyte composite membrane, the preparation method comprising: Graphene oxide and a reducing agent are uniformly dispersed in deionized water to obtain an aqueous solution of graphene oxide. The aqueous solution of graphene oxide is poured into a mold and heated to react and obtain graphene. The graphene obtained by the reaction is cooled and thawed to allow the graphene to connect and form a three-dimensional framework structure, generating graphene aerogel. After the first drying, a porous graphene aerogel membrane is obtained. The soluble salts corresponding to the metal elements contained in the inorganic solid electrolyte and the catalyst are dissolved in a first organic solvent to obtain an inorganic solid electrolyte precursor. The inorganic solid electrolyte precursor is filled into the pores of the graphene aerogel membrane by vacuum filtration. After a second drying, a graphene aerogel membrane with the inorganic solid electrolyte precursor filling the pores is obtained. The graphene aerogel membrane filled with inorganic solid electrolyte precursor in the pores is placed in a tube furnace and sintered in an inert atmosphere to generate inorganic solid electrolyte and attach it to the three-dimensional skeleton structure formed by the connection between the graphene molecules, forming a three-dimensional network structure, thus obtaining a graphene aerogel inorganic solid electrolyte composite membrane with pores. The organic solid electrolyte solution was filled into the pores of the graphene aerogel inorganic solid electrolyte composite membrane by vacuum filtration. After a third drying, the graphene aerogel organic-inorganic solid electrolyte composite membrane was obtained.
[0005] Preferably, the mass concentration of the graphene oxide aqueous solution is 0.1 g / L-10 g / L; In the aqueous solution of graphene oxide, the molar concentration of the reducing agent is 0.01 mol / L to 0.1 mol / L.
[0006] Preferably, the reducing agent includes one or more of hydroiodic acid, sodium iodide, sodium sulfide, ascorbic acid, dopamine, and melamine.
[0007] Preferably, the graphene oxide aqueous solution is heated in the mold at a temperature of 50°C-80°C for 6-8 hours.
[0008] Preferably, the cooling and thawing process is as follows: The graphene was placed in a freezing device and cooled to -15°C to -25°C for 3 to 6 hours, then removed and allowed to thaw naturally.
[0009] Preferably, the first drying is vacuum drying, with a vacuum degree of -0.08MPa to -0.1MPa, a temperature of 40℃ to 80℃, and a drying time of 12 hours to 48 hours; The temperature for the second drying is 40℃-80℃, and the drying time is 4 hours-12 hours. The third drying is vacuum drying, with a vacuum degree of -0.08MPa to -0.1MPa, a temperature of 60℃ to 80℃, and a drying time of 12 hours to 48 hours.
[0010] Preferably, sintering under an inert atmosphere specifically involves: Under an inert atmosphere, the temperature is increased to 800℃-900℃ at a rate of 1℃ / min-2℃ / min and held for 4-8 hours. Then, the temperature is increased to 1000℃-1100℃ at a rate of 1℃ / min-2℃ / min and held for 6-12 hours. Finally, the temperature is allowed to cool naturally to room temperature. During the sintering process, the flow rate of the inert gas is 30-50 mL / min.
[0011] Preferably, the organic solid electrolyte solution comprises a second organic solvent, a polymer, and a lithium salt, wherein the polymer accounts for 5%-15% of the total mass of the organic solid electrolyte solution, and the lithium salt accounts for 1%-5% of the total mass of the organic solid electrolyte solution.
[0012] Secondly, embodiments of the present invention provide a graphene aerogel inorganic-organic solid electrolyte composite membrane, wherein the graphene aerogel inorganic-organic solid electrolyte composite membrane is prepared by the preparation method described in the first aspect above.
[0013] Thirdly, embodiments of the present invention provide a lithium-ion battery, the lithium-ion battery comprising the graphene aerogel inorganic-organic solid electrolyte composite separator described in the second aspect above.
[0014] This invention provides a method for preparing a graphene aerogel inorganic-organic solid-state electrolyte composite separator. This method utilizes graphene oxide to prepare a graphene aerogel with a three-dimensional framework structure, increasing the mechanical strength of the separator. By attaching the inorganic solid-state electrolyte to the three-dimensional framework to form a three-dimensional network structure, the lithium-ion conductivity is increased. The addition of an organic solid-state electrolyte increases the separator's flexibility and further enhances its mechanical strength. The GA organic-inorganic solid-state electrolyte composite separator prepared by this method can be applied in lithium-ion batteries, improving both lithium-ion conductivity and safety. Attached Figure Description
[0015] The technical solutions of the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples.
[0016] Figure 1 A flowchart illustrating the preparation method of the graphene aerogel inorganic-organic solid electrolyte composite membrane provided in this embodiment of the invention; Figure 2 This is a scanning electron microscope (SEM) image of the graphene aerogel provided in Example 1 of the present invention. Figure 3 This is a schematic diagram of the structure of the graphene aerogel inorganic-organic solid electrolyte composite membrane prepared in Example 1 of the present invention. Detailed Implementation
[0017] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. However, it should be understood that these embodiments are only for more detailed description and should not be construed as limiting the present invention in any way, that is, not intended to limit the scope of protection of the present invention.
[0018] This invention provides a method for preparing a graphene aerogel inorganic-organic solid electrolyte composite membrane, such as... Figure 1 As shown, the preparation method mainly includes the following steps: Step 110: Graphene oxide (GO) and reducing agent are uniformly dispersed in deionized water to obtain GO aqueous solution. The GO aqueous solution is poured into a mold and heated to react and obtain graphene. The graphene obtained by the reaction is cooled and thawed to allow the graphene to connect and form a three-dimensional framework structure, generating graphene aerogel (GA). After the first drying, a porous GA membrane is obtained.
[0019] This step is mainly for preparing GA films. The GO used in this application is prepared using the Hummers method, and the reducing agent includes one or more of hydroiodic acid, sodium iodide, sodium sulfide, ascorbic acid, dopamine, and melamine. A certain mass of GO and a certain mass of reducing agent are taken, and the GO and reducing agent are uniformly dispersed in deionized water by stirring, sonication, etc., to obtain a GO aqueous solution with a mass concentration of 0.1 g / L-10 g / L. In the GO aqueous solution, the molar concentration of the reducing agent is 0.01 mol / L-0.1 mol / L.
[0020] Graphene can be obtained by pouring an aqueous solution of GO into a tetrafluoroethylene mold and heating it. Specifically, the heating temperature is 50℃-80℃ and the heating time is 6-8 hours. After heating, GO reacts with a reducing agent and GO is reduced to generate graphene.
[0021] Graphene undergoes at least one cooling and thawing process, causing the graphene molecules to connect and form a three-dimensional framework structure, generating GA. The GA is then vacuum-dried at 40℃-80℃ for 12-48 hours at a vacuum degree of -0.08MPa to -0.1MPa, resulting in a porous GA membrane. Specifically, the cooling and thawing process is as follows: Place the graphene in a freezing device (e.g., a refrigerator) and cool it to -15°C to -25°C. Keep it there for 3 to 6 hours, then remove it and let it thaw naturally.
[0022] Step 120: Dissolve the soluble salt corresponding to the metal element contained in the inorganic solid electrolyte and the catalyst in the first organic solvent to obtain the inorganic solid electrolyte precursor. By vacuum filtration, the inorganic solid electrolyte precursor is filled into the pores of the GA membrane. After a second drying, a GA membrane with the inorganic solid electrolyte precursor filled in the pores is obtained.
[0023] This step is mainly to fill the pores in the GA film using a solid electrolyte precursor. Specifically, in this application, the first organic solvent is one or more of ethanol and ethylene glycol methyl ether; the inorganic solid electrolyte includes one or more of lithium lanthanum titanium oxide (LLTO), lithium lanthanum zirconium oxide (LLZO), and lithium titanium aluminum phosphate (LATP), wherein the chemical formula of LATP is Li 1+ x Al x Ti2-x (PO4)3, x is between 0.01 and 0.5, and the soluble salts corresponding to the metal elements it contains include lithium nitrate (LiNO3), aluminum nitrate (Al(NO3)3), and tetrabutyl titanate (Ti(OC4H9)4); the chemical formula of LLTO is Li 3y La 2 / 3-y TiO3, with a y value between 0.01 and 0.5, contains soluble salts of metal elements including LiNO3, lanthanum nitrate (La(NO3)3·6H2O), and Ti(OC4H9)4; the chemical formula of LLZO is Li7La3ZrO. 12 The soluble salts corresponding to the metal elements contained include LiNO3, (La(NO3)3·6H2O), and zirconium n-butoxide (C 16 H 36 O4Zr).
[0024] The catalyst in this application is an organic acid, including one or more of acetic acid (HAC) and citric acid (C5H8O7), preferably HAC. Its function is to promote the formation of a sol in the organic solvent from the soluble salts corresponding to the metal elements contained in the inorganic solid electrolyte, thus generating an inorganic solid electrolyte precursor. The vacuum degree during vacuum filtration is -0.02 MPa to -0.1 MPa. The inorganic solid electrolyte precursor fills the pores of the GA membrane, at which point the pores disappear. However, after a second drying, the inorganic solid precursor gradually gels from the sol to form a colloid, at which point the pores reappear, resulting in a GA membrane with pores filled with the inorganic solid electrolyte precursor. The temperature of the second drying is 40℃-80℃, and the drying time is 4 hours-12 hours.
[0025] Step 130: Place the GA membrane filled with inorganic solid electrolyte precursor in a tube furnace and sinter it under an inert atmosphere to generate inorganic solid electrolyte and attach it to the three-dimensional framework structure formed by the connection between graphene, forming a three-dimensional network structure, and obtain a porous GA inorganic solid electrolyte composite membrane.
[0026] This step is mainly for sintering to obtain the GA inorganic solid electrolyte composite membrane. The inorganic solid electrolyte precursor is sintered to generate the inorganic solid electrolyte. Specifically, the sintering under an inert atmosphere involves: Under an inert atmosphere, the temperature is increased to 800℃-900℃ at a rate of 1℃ / min-2℃ / min and held for 4-8 hours. Then, the temperature is increased to 1000℃-1100℃ at a rate of 1℃ / min-2℃ / min and held for 6-12 hours. Finally, the temperature is allowed to cool naturally to room temperature. During the sintering process, the flow rate of the inert gas is 30-50 mL / min. The inert gas includes one or more of nitrogen, argon, and helium.
[0027] Step 140: The organic solid electrolyte solution is filled into the pores of the GA inorganic solid electrolyte composite membrane by vacuum filtration. After a third drying, the GA organic-inorganic solid electrolyte composite membrane is obtained.
[0028] This step is mainly to fill the pores in the GA inorganic solid electrolyte composite membrane with organic solid electrolyte. Specifically, the organic solid electrolyte solution includes a second organic solvent, a polymer and a lithium salt, wherein the polymer accounts for 5%-15% of the total mass of the organic solid electrolyte solution and the lithium salt accounts for 1%-5% of the total mass of the organic solid electrolyte solution.
[0029] The second organic solvent includes one or more of N,N-dimethylformamide (DMF), dimethylacetamide (DMAC), acetonitrile, acetone, dimethyl carbonate (DMC), ethylene carbonate (EC), and N-methylpyrrolidone (NMP).
[0030] The polymers include one or more of polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polycyanoacrylate (PCA), polyacrylate, and polyimide (PI).
[0031] Lithium salts include one or more of the following: lithium perchlorate (LiClO4), LiNO3, lithium fluoride (LiF), lithium bis(oxalate-borate)borate (LiBOB), lithium difluorooxalate-borate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), and lithium hexafluorophosphate (LiPF6).
[0032] In addition, during the vacuum filtration process in step 140, the vacuum degree is -0.02MPa to -0.1MPa, the third drying is vacuum drying with a vacuum degree of -0.08MPa to -0.1MPa, the temperature of the third drying is 60℃ to 80℃, and the time of the third drying is 12 hours to 48 hours.
[0033] This method utilizes graphene oxide to prepare graphene aerogel with a three-dimensional framework structure, increasing the mechanical strength of the separator. By attaching an inorganic solid electrolyte to the three-dimensional framework to form a three-dimensional network structure, the lithium-ion conductivity is increased. The addition of an organic solid electrolyte increases the separator's flexibility and further enhances its mechanical strength. The GA organic-inorganic solid electrolyte composite separator prepared by this method can be applied in lithium-ion batteries, improving both lithium-ion conductivity and safety.
[0034] Example 1 Example 1 provides a GA / LLTO / PEO composite membrane, the preparation steps of which are as follows: Step 1: Preparation of GA membrane Weigh 0.1g of GO and 0.176g of ascorbic acid, add them to 100mL of deionized water, and stir until homogeneous to obtain an aqueous GO solution. Pour the above solution into a tetrafluoroethylene mold and react at 80℃ for 8 hours. Then cool it to -20℃ in a refrigerator and keep it there for 3 hours before thawing naturally. Repeat the above cooling and thawing process 3 times. Then vacuum dry it at 60℃ for 48 hours to obtain a GA membrane.
[0035] Step 2: Prepare a GA membrane with LLTO precursor filling the pores. Weigh 1.60 g of LiNO3, 14.17 g of La(NO3)3·6H2O, 10 mL of Ti(OC4H9)4, and 4 mL of HAC, then dissolve them in 20 mL of ethanol. Stir at 50 °C and 200 rpm for 10 minutes to obtain the LLTO precursor. Adjust the vacuum degree of the filtration to -0.1 MPa and fill the pores of the GA membrane with the LLTO precursor. Then dry at 60 °C for 6 hours to obtain the GA membrane with the pores filled with the LLTO precursor.
[0036] Step 3: High-temperature sintering to obtain GA / LLTO membrane A GA membrane filled with LLTO precursor was placed in a tube furnace, and nitrogen gas was introduced at a flow rate of 40 mL / min. The temperature was programmed to rise to 900°C at a rate of 1°C / min and held for 4 hours. Then, the temperature was raised to 1100°C at a rate of 1°C / min and held for 6 hours. The membrane was then allowed to cool naturally to obtain a porous GA / LLTO membrane.
[0037] Step 4: PEO is used to fill the pores of the GA / LLTO membrane to prepare a GA / LLTO / PEO composite membrane. Weigh 176g of DMF, add 20g of PEO and 4g of LiTFSI at a stirring speed of 1000rpm, and stir for 6 hours to fully dissolve to obtain an organic solid electrolyte solution; fill the pores of the GA / LLTO membrane with the prepared organic solid electrolyte solution by vacuum filtration at a vacuum degree of -0.1MPa, and dry under vacuum at 80℃ for 48 hours to obtain the GA / LLTO / PEO composite membrane.
[0038] Figure 2 This is a scanning electron microscope (SEM) image of GA provided in Embodiment 1 of the present invention. Figure 3 This is a schematic diagram of the structure of the GA inorganic-organic solid electrolyte composite membrane prepared in Example 1 of this invention. Figure 2 , Figure 3It can be seen that the graphene molecules are connected to form a three-dimensional framework structure, which increases the mechanical strength of the membrane. The inorganic solid electrolyte is attached to the three-dimensional framework structure formed by the graphene molecules, forming a three-dimensional network structure. When the composite membrane is used in lithium-ion batteries, it can enhance the lithium-ion conduction efficiency. The organic electrolyte solute fills the pores of the GA inorganic solid electrolyte composite membrane, which increases the flexibility of the membrane and further enhances its mechanical strength.
[0039] Example 2 Example 2 provides a GA / LLZO / PEO composite membrane, the preparation steps of which are as follows: Step 1: Preparation of GA membrane Weigh 0.2g of GO and 0.352g of ascorbic acid, add them to 100mL of deionized water, and stir until homogeneous to obtain an aqueous GO solution. Pour the above solution into a tetrafluoroethylene mold and react at 80℃ for 8 hours. Then cool it to -20℃ in a refrigerator and keep it there for 3 hours before thawing naturally. Repeat the above cooling and thawing process 3 times. Dry it under vacuum at 60℃ for 48 hours to obtain a GA membrane.
[0040] Step 2: Prepare a GA membrane with LLZO precursor filling the pores. Weigh out 5.31g of LiNO3, 12.99g of La(NO3)3·6H2O, and 6.5mL of C 12 H 28 O4Zr and 4 mL of HAC were dissolved in 16 mL of ethylene glycol methyl ether and stirred at 50 °C and 200 rpm for 10 minutes to obtain an LLZO precursor. The vacuum degree of the filtration was adjusted to -0.1 MPa, and the LLZO precursor was filled into the pores of the GA membrane. Then, it was dried at 60 °C for 6 hours to obtain a GA membrane with the pores filled with the LLZO precursor.
[0041] Step 3: High-temperature sintering to obtain GA / LLZO membrane A graphene aerogel film filled with LLZO precursor was placed in a tube furnace, and nitrogen gas was introduced at a flow rate of 40 ml / min. The temperature was programmed to rise to 850°C at a rate of 1°C / min and held for 5 hours. Then, the temperature was raised to 1100°C at a rate of 1°C / min and held for 6 hours. The GA / LLZO membrane was obtained by natural cooling.
[0042] Step 4: PEO is used to fill the pores of the GA / LLZO membrane to prepare a GA / LLZO / PEO composite membrane. Weigh 176g of DMF, add 20g of PEO and 4g of LiTFSI at a stirring speed of 1000rpm, and stir for 6 hours to fully dissolve to obtain an organic solid electrolyte solution; fill the pores of the graphene aerogel GA / LLZO membrane with the prepared organic solid electrolyte solution by vacuum filtration, and vacuum dry at 80℃ for 48 hours to obtain the GA / LLZO / PEO composite membrane.
[0043] Example 3 Example 3 provides a GA / LLTO / PVDF composite membrane, the preparation steps of which are as follows: Step 1: Preparation of GA membrane Weigh 0.01g of GO and 1.499g of sodium iodide, add them to 100mL of deionized water, and stir until homogeneous to obtain an aqueous GO solution. Pour the above solution into a tetrafluoroethylene mold and react at 50℃ for 6 hours. Then cool it to -15℃ in a refrigerator and keep it there for 6 hours before thawing naturally. Repeat the above cooling and thawing process 3 times. Then dry it under vacuum at 40℃ for 24 hours to obtain a GA membrane.
[0044] Step 2: Prepare a GA membrane with LLTO precursor filling the pores. Weigh 1.60 g of LiNO3, 14.17 g of La(NO3)3·6H2O, 10 mL of Ti(OC4H9)4, and 5 mL of CH3COOH, then dissolve them in 30 mL of ethylene glycol methyl ether. Stir at 50 °C and 300 rpm for 10 minutes to obtain the LLTO precursor. Adjust the vacuum degree of the filtration to -0.01 MPa, fill the pores of the GA membrane with the LLTO precursor, and then dry at 40 °C for 12 hours to obtain the GA membrane with the pores filled with the LLTO precursor.
[0045] Step 3: High-temperature sintering to obtain GA / LLTO membrane A GA membrane filled with LLTO precursor was placed in a tube furnace, and nitrogen gas was introduced at a flow rate of 30 mL / min. The temperature was programmed to rise to 800°C at a rate of 2°C / min and held for 8 hours. Then, the temperature was raised to 1000°C at a rate of 2°C / min and held for 12 hours. The membrane was then allowed to cool naturally to obtain a porous GA / LLTO membrane.
[0046] Step 4: Fill the pores of the GA / LLTO membrane with PVDF to prepare a GA / LLTO / PVDF composite membrane. Weigh 189g of NMP, add 10g of PVDF and 1g of LiNO3 at a stirring speed of 1000rpm, and stir for 6 hours to fully dissolve to obtain an organic solid electrolyte solution; fill the pores of the GA / LLTO membrane with the prepared organic solid electrolyte solution by vacuum filtration at a vacuum degree of -0.02MPa, and dry under vacuum at 60℃ for 40 hours to obtain the GA / LLTO / PVDF composite membrane.
[0047] Example 4 Example 4 provides a GA / LLTO / PMMA composite membrane, the preparation steps of which are as follows: Step 1: Preparation of GA membrane Weigh 1g of GO and 1.532g of dopamine, add them to 100mL of deionized water, and stir until homogeneous to obtain an aqueous GO solution. Pour the above solution into a tetrafluoroethylene mold and react at 70℃ for 6 hours. Then cool it to -25℃ in a refrigerator and keep it there for 4 hours before thawing naturally. Repeat the above cooling and thawing process 3 times. Then dry it under vacuum at 80℃ for 12 hours to obtain a GA membrane.
[0048] Step 2: Prepare a GA membrane with LLTO precursor filling the pores. Weigh 1.60 g of LiNO3, 14.17 g of La(NO3)3·6H2O, 10 mL of Ti(OC4H9)4, and 4 mL of HAC, then dissolve them in 30 mL of ethanol. Stir at 50 °C and 200 rpm for 10 minutes to obtain the LLTO precursor. Adjust the vacuum degree of the filtration to -0.02 MPa, fill the pores of the GA membrane with the LLTO precursor, and then dry at 80 °C for 4 hours to obtain the GA membrane with the pores filled with the LLTO precursor.
[0049] Step 3: High-temperature sintering to obtain GA / LLTO membrane A GA membrane filled with LLTO precursor was placed in a tube furnace, and nitrogen gas was introduced at a flow rate of 50 mL / min. The temperature was programmed to rise to 850°C at a rate of 2°C / min and held for 6 hours. Then, the temperature was raised to 1050°C at a rate of 2°C / min and held for 8 hours. The membrane was then allowed to cool naturally to obtain a porous GA / LLTO membrane.
[0050] Step 4: Fill the pores of the GA / LLTO membrane with PMMA to prepare a GA / LLTO / PMMA composite membrane. Weigh 172g of acetonitrile, add 20g of PMMA and 8g of LiPF6 at a stirring speed of 1000rpm, and stir for 6 hours to fully dissolve to obtain an organic solid electrolyte solution; fill the pores of the GA / LLTO membrane with the prepared organic solid electrolyte solution by vacuum filtration at a vacuum degree of -0.01MPa, and dry under vacuum at 70℃ for 12 hours to obtain a GA / LLTO / PMMA composite membrane.
[0051] Comparative Example 1 Compared to Example 1, this comparative example uses graphene (GN), but does not prepare GN into GA. Specifically, it provides a GN / LLTO / PEO composite membrane, the preparation steps of which are as follows: Step 1: Preparation of GN powder Take 2g of GO and 1.76g of ascorbic acid, add them to 1000mL of deionized water, stir well to obtain GO aqueous solution, react at 80℃ for 24 hours, and spray dry to obtain GN powder.
[0052] Step 2: Preparation of LLTO powder by sol-gel method Weigh 1.60 g of LiNO3, 14.17 g of La(NO3)3·6H2O, 10 mL of Ti(OC4H9)4, and 4 mL of HAC, and dissolve them in 20 mL of ethanol. Stir at 50 °C and 200 rpm for 10 minutes to obtain LLTO precursor sol. After aging for 12 hours, dry at 80 °C under a vacuum of -0.1 MPa for 6 hours, and then grind to obtain LLTO precursor. Place the LLTO precursor in a tube furnace under an argon atmosphere and heat it to 900 °C at a programmed heating rate of 1 °C / min. Hold for 4 hours, then heat it to 1100 °C at a heating rate of 1 °C / min and hold for 6 hours. Allow it to cool naturally to obtain LLTO powder.
[0053] Step 3: Prepare GN / LLTO / PEO dispersion Weigh 171g of DMF, 20g of PEO, 5g of LLTO powder, 4g of LiTFSI, 0.2g of GN powder, and 0.05g of dispersant PEG400, and stir at 600rpm for 6 hours to obtain a uniformly dispersed GN / LLTO / PEO dispersion.
[0054] Step 4: Preparation of GN / LLTO / PEO composite membrane The GN / LLTO / PEO dispersion was poured into a tetrafluoroethylene mold and dried under vacuum at 80°C for 48 hours to obtain a GN / LLTO / PEO composite membrane.
[0055] Comparative Example 2 Compared with Example 1, this comparative example did not use GN, but specifically provided an LLTO / PEO composite membrane, the preparation steps of which are as follows: Step 1: Preparation of LLTO powder by sol-gel method Weigh 1.60 g of LiNO3, 14.17 g of La(NO3)3·6H2O, 10 mL of Ti(OC4H9)4, and 4 mL of HAC, and dissolve them in 20 mL of ethanol. Stir at 50 °C and 200 rpm for 10 minutes to obtain LLTO precursor sol. After aging for 12 hours, dry at 80 °C under a vacuum of -0.1 MPa for 6 hours, and then grind to obtain LLTO precursor. Place the LLTO precursor in a tube furnace under an argon atmosphere and heat it to 900 °C at a rate of 1 °C / min. Hold for 4 hours, then heat it to 1100 °C at a rate of 1 °C / min and hold for 6 hours. Allow it to cool naturally to obtain LLTO powder.
[0056] Step 2: Prepare LLTO / PEO dispersion Weigh 171g of DMF, 20g of PEO, 5g of LLTO powder, and 4g of LiTFSI, and stir at 600rpm for 6 hours to obtain a uniformly dispersed LLTO / PEO dispersion.
[0057] Step 3: Preparation of LLTO / PEO composite membrane The LLTO / PEO dispersion was poured into a tetrafluoroethylene mold and dried under vacuum at 80°C for 48 hours to obtain an LLTO / PEO composite membrane.
[0058] Comparative Example 3 Compared to Example 2, this comparative example uses GN instead of GA. Specifically, it provides a GN / LLZO / PEO composite membrane, the preparation steps of which are as follows: Step 1: Preparation of GN Weigh 2g of GO and 1.76g of ascorbic acid, add them to 1000mL of deionized water, stir well to obtain GO aqueous solution, react at 80℃ for 24 hours, and spray dry to obtain GN powder.
[0059] Step 2: Preparation of LLZO powder by sol-gel method Weigh out 5.31g of LiNO3, 12.99g of La(NO3)3·6H2O, and 6.5mL of C 12 H 28O4Zr and 4 mL of HAC were dissolved in 16 mL of ethylene glycol methyl ether and stirred at 50 °C and 200 rpm for 10 minutes to obtain LLZO precursor. After aging for 12 hours, it was dried at 80 °C under a vacuum of -0.1 MPa for 6 hours and then ground to obtain LLZO precursor. The LLZO precursor was placed in a tube furnace under an argon atmosphere and heated to 850 °C at a rate of 1 °C / min, held for 5 hours, and then heated to 1100 °C at a rate of 1 °C / min, held for 6 hours, and then cooled naturally to obtain LLZO powder.
[0060] Step 3: Prepare graphene powder / LLZO / PEO dispersion Weigh 171g of DMF, 20g of PEO, 5g of LLZO powder, 4g of LiTFSI, 2g of GN powder, and 0.05g of dispersant PEG400. Stir at 600rpm for 6 hours to obtain a uniformly dispersed GN / LLZO / PEO dispersion.
[0061] Step 4: Preparation of GN / LLZO / PEO composite membrane The GN / LLZO / PEO dispersion was poured into a tetrafluoroethylene mold and dried under vacuum at 80°C for 48 hours to obtain a GN / LLZO / PEO composite membrane.
[0062] Comparative Example 4 Compared with Example 2, this comparative example did not use GN, but specifically provided an LLZO / PEO composite membrane, the preparation steps of which are as follows: Step 1: Preparation of LLZO powder by sol-gel method Weigh out 5.31g of LiNO3, 12.99g of La(NO3)3·6H2O, and 6.5mL of C 12 H 28 O4Zr and 4 mL of HAC were dissolved in 16 mL of ethylene glycol methyl ether and stirred at 50 °C and 200 rpm for 10 minutes to obtain LLZO precursor. After aging for 12 hours, it was dried at 80 °C under a vacuum of -0.1 MPa for 6 hours and then ground to obtain LLZO precursor. The LLZO precursor was placed in a tube furnace under an argon atmosphere and heated to 850 °C at a rate of 1 °C / min, held for 5 hours, and then heated to 1100 °C at a rate of 1 °C / min, held for 6 hours, and then cooled naturally to obtain LLZO powder.
[0063] Step 2: Prepare LLZO / PEO dispersion Weigh 171g of DMF, 20g of PEO, 5g of LLZO powder, and 4g of LiTFSI, and stir at 600rpm for 6 hours to obtain a uniformly dispersed LLZO / PEO dispersion.
[0064] Step 3: Preparation of LLZO / PEO composite membrane The LLZO / PEO dispersion was poured into a tetrafluoroethylene mold and dried under vacuum at 80°C for 48 hours to obtain an LLZO / PEO composite membrane.
[0065] To verify the superiority of the preparation method for GA organic-inorganic solid electrolyte composite membrane provided by the present invention, the composite membranes prepared in Examples 1, 2 and Comparative Examples 1-4 were tested for ionic conductivity, membrane thickness and tensile strength. The test results are listed in Table 1.
[0066] The test methods for ionic conductivity, film thickness, and tensile strength are as follows: Tensile strength: determined according to national standard GB / T 1040.3-2006.
[0067] Film thickness: Measured according to industrial standard SJ / T 101.1-91.
[0068] Ionic conductivity: determined by electrochemical impedance spectroscopy (EIS). Specifically, stainless steel was used as the blocking electrode, the EIS test frequency range was 5MHz-1Hz, the test temperature range was -20-80℃, and the perturbation voltage was 10mV.
[0069] Table 1 Comparing the data of Example 1 with Comparative Examples 1 and 2 in Table 1, it can be seen that the tensile strength and ionic conductivity of Example 1 are superior to those of Comparative Examples 1 and 2. This is because, compared with Comparative Examples 1 and 2, (1) Example 1 contains GA with a three-dimensional skeleton structure, which enhances the mechanical strength of the membrane; (2) the inorganic solid electrolyte in Example 1 is attached to the three-dimensional skeleton structure, forming a three-dimensional network structure, which enhances the lithium-ion conduction efficiency; (3) the organic solid electrolyte in Example 1 fills the pores in the GA inorganic solid electrolyte membrane, which not only increases the flexibility of the membrane but also increases its mechanical strength. The data in Comparative Examples 2, 3, and 4 also confirm the above conclusions.
[0070] This invention provides a method for preparing a graphene aerogel inorganic-organic solid-state electrolyte composite separator. This method utilizes graphene oxide to prepare a graphene aerogel with a three-dimensional framework structure, increasing the mechanical strength of the separator. By attaching the inorganic solid-state electrolyte to the three-dimensional framework to form a three-dimensional network structure, the lithium-ion conductivity is increased. The addition of an organic solid-state electrolyte increases the separator's flexibility and further enhances its mechanical strength. The GA organic-inorganic solid-state electrolyte composite separator prepared by this method can be applied in lithium-ion batteries, improving both lithium-ion conductivity and safety.
[0071] The above specific embodiments further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a graphene aerogel inorganic-organic solid electrolyte composite membrane, characterized in that, The preparation method includes: Graphene oxide and a reducing agent are uniformly dispersed in deionized water to obtain an aqueous solution of graphene oxide. The aqueous solution of graphene oxide is poured into a mold and heated to react and obtain graphene. The graphene obtained by the reaction is cooled and thawed to allow the graphene to connect and form a three-dimensional framework structure, generating graphene aerogel. After the first drying, a porous graphene aerogel membrane is obtained. The soluble salts corresponding to the metal elements contained in the inorganic solid electrolyte and the catalyst are dissolved in a first organic solvent to obtain an inorganic solid electrolyte precursor. The inorganic solid electrolyte precursor is filled into the pores of the graphene aerogel membrane by vacuum filtration. After a second drying, a graphene aerogel membrane with the inorganic solid electrolyte precursor filling the pores is obtained. The graphene aerogel membrane filled with inorganic solid electrolyte precursor in the pores is placed in a tube furnace and sintered in an inert atmosphere to generate inorganic solid electrolyte and attach it to the three-dimensional skeleton structure formed by the connection between the graphene molecules, forming a three-dimensional network structure, thus obtaining a graphene aerogel inorganic solid electrolyte composite membrane with pores. The organic solid electrolyte solution was filled into the pores of the graphene aerogel inorganic solid electrolyte composite membrane by vacuum filtration. After a third drying, the graphene aerogel organic-inorganic solid electrolyte composite membrane was obtained.
2. The preparation method according to claim 1, characterized in that, The mass concentration of the graphene oxide aqueous solution is 0.1 g / L-10 g / L; In the aqueous solution of graphene oxide, the molar concentration of the reducing agent is 0.01 mol / L to 0.1 mol / L.
3. The preparation method according to claim 1, characterized in that, The reducing agent includes one or more of hydroiodic acid, sodium iodide, sodium sulfide, ascorbic acid, dopamine, and melamine.
4. The preparation method according to claim 1, characterized in that, The graphene oxide aqueous solution is heated in the mold at a temperature of 50℃-80℃ for 6-8 hours.
5. The preparation method according to claim 1, characterized in that, The cooling and thawing process is as follows: The graphene was placed in a freezing device and cooled to -15°C to -25°C for 3 to 6 hours, then removed and allowed to thaw naturally.
6. The preparation method according to claim 1, characterized in that, The first drying is vacuum drying, with a vacuum degree of -0.08MPa to -0.1MPa, a temperature of 40℃ to 80℃, and a drying time of 12 hours to 48 hours; The temperature for the second drying is 40℃-80℃, and the drying time is 4 hours-12 hours. The third drying is vacuum drying, with a vacuum degree of -0.08MPa to -0.1MPa, a temperature of 60℃ to 80℃, and a drying time of 12 hours to 48 hours.
7. The preparation method according to claim 1, characterized in that, Sintering under an inert atmosphere specifically involves: Under an inert atmosphere, the temperature is increased to 800℃-900℃ at a rate of 1℃ / min-2℃ / min and held for 4-8 hours. Then, the temperature is increased to 1000℃-1100℃ at a rate of 1℃ / min-2℃ / min and held for 6-12 hours. Finally, the temperature is allowed to cool naturally to room temperature. During the sintering process, the flow rate of the inert gas is 30-50 mL / min.
8. The preparation method according to claim 1, characterized in that, The organic solid electrolyte solution comprises a second organic solvent, a polymer, and a lithium salt, wherein the polymer accounts for 5%-15% of the total mass of the organic solid electrolyte solution, and the lithium salt accounts for 1%-5% of the total mass of the organic solid electrolyte solution.
9. A graphene aerogel inorganic-organic solid electrolyte composite membrane, characterized in that, The graphene aerogel inorganic-organic solid electrolyte composite membrane is prepared by the preparation method described in any one of claims 1-8.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the graphene aerogel inorganic-organic solid electrolyte composite separator as described in claim 9.
Citation Information
Patent Citations
Lithium battery polymer solid electrolyte membrane with high and low temperature stability and preparation method thereof
CN112701359A
Compact solid electrolyte of lithium battery and preparation method of compact solid electrolyte
CN113299980A